Novel Conservative Approach to High Surgical Risk Frail Proximal Femur Fractures - Alexander Koizia; Ala Abuown; Julie Vowles; Damien Smith; Louis J. Koizia (Case Reports in Orthopedics)
One of the major impacts following a neck of femur fracture is pain. Most patients (nearly all) undergo an operation. This usually includes the frailest terminal patients and deemed a palliative procedure to reduce ongoing pain. The operation comes with risks and can reduce life expectancy in these patients and result in prolonged hospital admission, delirium, and postoperative complications. This case highlights a novel approach to managing the frailest end-of-life patients that does not require them to undergo a conventional operation. The case resulted in a quick discharge from hospital and for the patient and family to maximise the time out of hospital, with a reduced analgesic burden and a peaceful passing away. We feel that this could be an alternative, more humane option for such patients.